Loving Out Loud: Community Mentors, Teacher Candidates, and Transformational Learning Through a Pedagogy of Care and Connection. (March 2018) - Zygmunt, Eva; Cipollone, Kristin; Tancock, Susan; Clausen, Jon; Clark, Patricia; Mucherah, Winnie
Although there has been significant research examining the practice of culturally responsive teaching, little empirical work to date has examined the role that community-engaged, teacher preparation models play in shaping prospective teachers' orientation toward cultural responsiveness. This study of 60 preservice teacher candidates enrolled in a program of community-engaged teacher preparation at a midsized Midwestern public university specifically examined the ways in which caring relationships between preservice teachers and volunteer community mentors scaffolded candidates' contextualized understanding of culture, community, and identity of children and families. Findings provide evidence that as candidates experience authentic caring within the space of supportive relationships, they emerge equipped to care in more authentic, culturally responsive ways for their students.